Mitochondrial Genomics of Six Cacao Pathogens From the Basidiomycete Family Marasmiaceae - Ali, Shahin S.; Amoako-Attah, Ishmael; Shao, Jonathan; Kumi-Asare, Eric; Meinhardt, Lyndel W.; Bailey, Bryan A. (Frontiers in Microbiology, 2021)
Thread blight disease has recently been described as an emerging disease on cacao (Theobroma cacao) in Ghana. In Ghana, thread blight disease is caused by multiple species of the Marasmiaceae family: Marasmius tenuissimus, M. crinis-equi, M. palmivorus and Marasmiellus scandens. Interestingly, two additional members of the Marasmiaceae; Moniliophthora roreri (frosty pod rot) and Moniliophthora perniciosa (witches’ broom disease), are major pathogens of cacao in the Western hemisphere. It is important to accurately characterize the genetic relationships among these economically important species in support of their disease management. We used data from Illumina NGS-based genome sequencing efforts to study the mitochondrial genomes (mitogenomes) of the four cacao thread blight associated pathogens from Ghana and compared them with published mitogenomes of Mon. roreri and Mon. perniciosa. There is a remarkable interspecies variation in mitogenome size within the six cacao-associated Marasmiaceae species, ranging from 43,121 bp to 109,103 bp. The differences in genome lengths are primarily due to the number and lengths of introns, differences in intergenic space, and differences in the size and numbers of unidentified ORFs (uORF). Among 7 M. tenuissimus mitogenomes sequenced, there is variation in size and sequence pointing to divergent evolution patterns within the species. The intronic regions show a high degree of sequence variation compared to the conserved sequences of the 14 core genes. The intronic ORFs identified, regardless of species, encode GIY-YIG or LAGLIDADG domain-containing homing endonuclease genes. Phylogenetic relationships using the 14 core proteins largely mimic the phylogenetic relationships observed in gene order patterns, grouping M. tenuissimus with M. crinis-equi, and M. palmivorus with Mon. roreri and Mon. perniciosa, leaving Mar. scandens as an outlier. The results from this study provide evidence of independent expansion/contraction events and sequence diversification in each species and establish a foundation for further exploration of the evolutionary trajectory of the fungi in Marasmiaceae family.